Ravin's Psychosocial Development in Ravinder Singh's Can Love Happen Twice? - Hendrik Sabtiyan Parasandi (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Psychosocial development is formed by 'psychology' and 'social' which consists of several stages or steps that individuals must undergo where it is rooted from the idea of Erik Erikson that individuals’ lives are affected by environmental factors. The stages of psychosocial development are started from early new born until death where during this journey, individuals may also experience some conflicts that serves as a self-learning to build some psychological qualities, personal growth or even failure or maldevelopment psychological qualities. This research is aimed to analyze the psychosocial development experienced by the main character named Ravin in Ravinder Singh’s Can Love Happen Twice?. Through psychosocial development theory by Erik Erikson, this research discovered that Ravinder Singh’s “Can Love Happen Twice?” is focusing specifically on Ravin’s journey in searching for his love, or his intimacy therefore, this research specifically analyze Ravin’s sixth stage of his psychosocial development (Young adulthood period; Intimacy vs Isolation). This research found that there are several conflicts related to Ravin’s intimacy such as his plan to get married with Simar, and Ravin’s isolation such as his depression after Simar rejected his idea to marry her. As it is stated by psychosocial development theory that each conflict can cause positive virtue or failure. This research also found that Ravin is able to escape from his isolation or depression and develop love or self-love through his plan to write his second bestseller book.